2018
DOI: 10.21608/mjfmct.2018.47199
|View full text |Cite
|
Sign up to set email alerts
|

A Study of Clinical and Laboratory Picture of Acute Tramadol Toxicity in Damietta Governorate

Abstract: Increased rate of seizures and respiratory complications due to tramadol poisoning have been observed, even with first time of tramadol intake. So, the present work was used to investigate the clinical manifestations and laboratory investigations of acute tramadol toxicity and the correlation between toxic tramadol manifestations and blood tramadol level and laboratory parameters. A study was performed on 100 patients (80 males and 20 females) acutely intoxicated with tramadol, admitted to toxicology unit of A… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 12 publications
1
1
0
Order By: Relevance
“…Some studies have reported hypoglycemia in tramadol poisoning [5,8,[27][28][29][30][31][32][33][34][35][36] and others have reported elevated blood glucose levels in these individuals [31,37,38]. Consistent with our results, several studies have shown normal blood glucose levels in people with tramadol poisoning [4,8,31,34,36,39,40]. The different results in different studies can be attributed to differences in the samples studied, different doses of tramadol, different measurement times of BGL, and various methods of administration.…”
Section: Discussionsupporting
confidence: 91%
“…Some studies have reported hypoglycemia in tramadol poisoning [5,8,[27][28][29][30][31][32][33][34][35][36] and others have reported elevated blood glucose levels in these individuals [31,37,38]. Consistent with our results, several studies have shown normal blood glucose levels in people with tramadol poisoning [4,8,31,34,36,39,40]. The different results in different studies can be attributed to differences in the samples studied, different doses of tramadol, different measurement times of BGL, and various methods of administration.…”
Section: Discussionsupporting
confidence: 91%
“…Patients with recurrent seizures ingested, on average double the tramadol dose of single seizure patients [10]. In contrast, some studies reported a non-significant difference of serum tramadol concentrations between patients with seizures and those without seizures [2,17,73,74].…”
Section: Central Nervous Systemmentioning
confidence: 99%